Development of the anticitrullinated peptide antibody repertoire prior to the onset of rheumatoid arthritis. (22nd February 2011) - van de Stadt, L A; de Koning, M H M T; van de Stadt, R J; Wolbink, G; Dijkmans, B A C; Hamann, D; van Schaardenburg, D
Abstract : Background: Anticitrullinated protein antibodies (ACPA) probably play a pathogenic role in rheumatoid arthritis (RA). The ACPA response is already expanded before the first symptoms of RA and hardly changes thereafter. Objectives: To explore the degree of ACPA epitope spreading prior to onset of clinical RA and the pattern of auto-antigen reactivity at the beginning of the immune response. Methods: Multiple serial serum samples of 79 RA patients who had donated blood before disease onset were available for analysis. 47 patients tested ACPA (anti-CCP2) positive prior to the onset of clinical RA. Of these patients a median of 6 (IQR 4–9) sequential pre-RA sera spaced 1–2 years apart were tested for reactivity to five distinct citrullinated peptides in an ELISA. Two fibrinogen peptides, 1 vimentin, 1 α-enolase and 1 cyclic citrullinated peptide (CCP1) were tested. Results: Four out of 47 ACPA positive patients (9%) did not show reactivity to any peptide. In 23 ACPA positive patients seroconversion from ACPA absence to ACPA presence was observed. In 16 (70%) of these patients, the immune response started with reactivity towards one peptide, without preference for a particular peptide. In two patients (9%) it started with two peptides, in three (13%) it started with three peptides and in two (9%) it started with four peptides. The number of recognised peptides increased over time, without a dominant epitope spreading pattern. Median titres of all measured ACPA increased over time in a biphasic manner. Conclusion: ACPA epitope spreading occurs over several years prior to onset of clinical RA. None of the tested auto-antigens is solely responsible for the initial auto-immune response. ACPA epitope spreading is a random process. ACPA titers increase in a biphasic way, suggesting a 'second event' a few years before diagnosis of RA.